Game design workshop a playcentric approach to creating innovative games - Fullerton, Tracy (CRC Press, 2019)
Discover an exercise-driven, non-technical approach to game design, without the need for programming or artistic expertise with Game Design Workshop, Fourth Edition. Tracy Fullerton demystifies the creative process with clear and accessible analysis of the formal and dramatic systems of game design. Using examples of popular games, illustrations of design techniques, and refined exercises to strengthen your understanding of how game systems function and give you the skills and tools necessary to create a compelling and engaging game. Game Design Workshop puts you to work prototyping, playtesting, and revising your own games with time-tested methods and tools. These skills will provide the foundation for your career in any facet of the game industry including design, producing, programming, and visual design.